(3GdESJHUGQs - (3eMeO Hf GdMSf Hf Ydj GdWhSj , CHh LYaQ,J (B460 (3g` s ((3eMeO Hf EHQGgje Hf eMeO Hf eQLGJ s)
(3ChdgG (B:s
(3bGd cJH Edi HYV ENhGfi Cf GSFd CHGYHO Gddg Ydjg GdSdGe Yf eSGFd ef GdSjQ CNHQfi Yf GdLjT EPG ZRh CQV GdMQH s
(3BNQgG (B:s
(3CHhGH GdcJGH JSYeGFI hNeSI hYTQhf HGHkG jTJed Ydi hGddg Gdehab ddUhGH Je GdcJGH hgh cJGH GdESJHUGQ s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B84 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B202s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B266s
Keywords: (3GdMOjK h GdeUWdMs